EFFECT OF COOPERATIVE LEARNING MODEL TYPE THINK PAIR AND SHARE (TPS) ON STUDENT COOPERATION (Quasi Experiments on Social Studies Learning Class VII in 1 Cikajang Junior High School) - Qurtubhi, Wildan Muhammad (Universitas Pendidikan Indonesia, 2017)
Abstract-This study aims to test how much influence the model of cooperative learning type think pair and share (tps) on student cooperation (quasi experiment on social studies learning class VII in Cikajang Junior High School). The design used in this research is non-equevalent controlgroup with